REVITALIZATION OPPORTUNITIES OF BROWNFIELDS IN GAIGALAVA PARISH - Bikovska, Sintija; Matisovs, Ivars (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2018)
Brownfields are the result of social and economic change, which limits the further use and development of these areas. To promote sustainable development, it is possible to rehabilitate non-managed areas through revitalization projects. The restoration of brownfields offers benefits such as improved landscape quality, the useful use of land, territory, the return of economic activities to renewed areas. The study includes a survey of the degraded territories of the Gaigalava rural municipality, the analysis of land parcels of six sites and a detailed review of one territory, assessing the possibilities of restoring brownfields.